(3eNJUQ TQM eYGfi GdBKGQs - (3eMeO Hf CMeO Hf CMeO Hf QTO GdeGdcj GdbQWHj GdCfOdSj, GdbGVj CHh GdhdjO (B( (3GdLO (B)(3, J (B520 (3g` s; (3CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROqj GdWMGhj, CHh LYaQ,J (B321 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPG cJGH eNJUQ TQM eYGfi GdBKGQ ddWMGhi HGH GdeGA JbY ajg GdfLGSI PcQ CHh LYaQ QMeg Gddg JYGdi eG Qhi Yf CHj SYjO GdNOQi QVi Gddg Yfg Cf QShd Gddg Udi Gddg Ydjg hSde cGf jJhVC ef HFQ HVGYI s
(3BNQgG (B:s
(3jfJgi HHGH ZQI GdLfjf def gi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdMOjK h GdeUWdMs